PENERAPAN METODE USER CENTERED DESIGN (UCD) PADA SISTEM PEMESANAN MENU KULINER NUSANTARA BERBASIS MOBILE ANDROID - Bayu Priyatna (Ma'soem University, 2019)
The use of the Android platform for software / application development is not only easier to use, because Android that has flexibility is a reason. Rendang Daging is a typical food of the city of Padang, besides it tastes savory and has a taste that is very different from other processed foods, which makes the food rendang a favorite of many people around the world. It is unfortunate if only rendang is the favorite processed food menu, while in Indonesia there are still many processed menus that are very tasty and special. Information about the menu of typical Indonesian processed foods will be much better known and desirable when given a place to exchange information about these things in the form of information systems. To get an information system that meets user expectations, special methods are needed. (UCD) is a User-Centered Design method which is a user-oriented method. UCD design is used to provide benefits to support the information system for people from home and abroad so that it will be more attractive for foreign and domestic tourists to visit Indonesia for a vacation or just want to enjoy the typical food of the archipelago. In addition, it can also help the system of selling processed foods typical of the archipelago.